2022
DOI: 10.1016/j.jhealeco.2022.102589
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination strategies and transmission of COVID-19: Evidence across advanced countries

Abstract: Given limited supply of approved vaccines and constrained medical resources, design of a vaccination strategy to control a pandemic is an economic problem. We use time-series and panel methods with real-world country-level data to estimate effects on COVID-19 cases and deaths of two key elements of mass vaccination - time between doses and vaccine type. We find that new infections and deaths are both significantly negatively associated with the fraction of the population vaccinated with at least one dose. Cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
(42 reference statements)
1
14
0
Order By: Relevance
“…In particular, government responses of countries to cope with COVID-19 can have a high degree of strictness, such as a long period of full lockdown and quarantine, general travel bans at domestic and international level, compulsory facemask coverings indoors and outdoors, and widespread impositions to circulation of people that reduce public and private life in society, etc. (Allen 2022 ; Askitas et al 2021 ; Kim and Lee 2022 ; Wieland 2020 ). The strictness of policy responses to face COVID-19 pandemic crisis can be measured with a combination of different indicators that are aggregated in the stringency index, which is processed by the Oxford Coronavirus Government Response Tracker project (Hale et al 2021 ; Stringency Index 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, government responses of countries to cope with COVID-19 can have a high degree of strictness, such as a long period of full lockdown and quarantine, general travel bans at domestic and international level, compulsory facemask coverings indoors and outdoors, and widespread impositions to circulation of people that reduce public and private life in society, etc. (Allen 2022 ; Askitas et al 2021 ; Kim and Lee 2022 ; Wieland 2020 ). The strictness of policy responses to face COVID-19 pandemic crisis can be measured with a combination of different indicators that are aggregated in the stringency index, which is processed by the Oxford Coronavirus Government Response Tracker project (Hale et al 2021 ; Stringency Index 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kim & Lee ( 2022 ) argue that COVID-19 related infections and deaths are both negatively associated with the fraction of the population vaccinated with at least one dose. These scholars support, in the short term, the heath policy of extending the interval between first and second dose of administering COVID-19 vaccines associated with non-pharmaceutical measures of control.…”
Section: Resultsmentioning
confidence: 99%
“…However, our findings are consistent with previous prospective simulation studies that explored optimal vaccination strategies under different assumptions of VE, stringency of NPIs, vaccine mode of action, and waning immunity. These studies also found that prioritising partial protection of a larger proportion of the population by increasing the dosing interval could reduce the number of hospitalisations and deaths [13][14][15][16][17] . Barmpounakis et al found that the optimal strategy was to prioritise fully vaccinating the most elderly, before switching to a delayed second dose strategy for those under 75 years 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have explored the potential impact and optimisation of mass vaccination schedules under different assumptions of vaccine effectiveness (VE), vaccine mode of action, waning immunity, and the degree of non-pharmaceutical interventions (NPIs) in place 13,14 . They highlighted that more hospitalisations and deaths could be prevented by adopting a delayed second dose strategy, but that results were particularly sensitive to VE assumptions and vaccine mechanisms, underscoring the importance of continued NPIs 15–17 .…”
Section: Introductionmentioning
confidence: 99%